(untitled) (Global Journal of Medical Research, 2022)
The excessive intake of sodium from salt is associated with the risk of cardiovascular diseases According to the Noncommunicable Diseases Survey DNS N P more than 35 of the Cape Verdean population is considered hypertensive There are no data on the salt content of foods prepared by restaurants and bakeries in Cape Verde Most restaurants and bakeries use iodized salt 97 of national origin 81 from the islands of Sal 45 6 and Maio 20 9 Approximately 53 3 of the bread samples had salt contents greater than 1 4 g 100 g More than half 59 3 of ready-to-eat meals collected from restaurants in Praia and 42 4 in Mindelo had a salt content equal or more than 5 0 g meal Restaurants and bakeries in the cities of Praia and Mindelo use salt in a nonstandardized manner The results of this study may contribute to the redesign of salt intake reduction strategies in Cape Verde